Implementation of Line Follower Robot for Food Delivery Robot - Aisyah, Risa; Latifah, Ayu; Hidayatulloh, Endang Prayoga; ., Nurhidayat; Kifti, Jalaludin; Sodikin, M Fitroh; Alfiyah, Bintang Nur (Universitas Sebelas Maret (UNS), 2024)
A line follower robot is a robotic system capable of autonomous navigation by following a predefined path using optical sensors. This research focuses on the development of a line follower robot for food delivery in the food and beverage industry, particularly in restaurants, cafes, and eateries. The industry faces challenges such as low service efficiency and long order waiting times, which can lead to customer dissatisfaction. The objective of this research is to build a robot that can enhance service efficiency and overall customer experience. The method used is action research following Kurt Lewin's model, which includes planning, implementation, observation, and reflection stages. The developed robot is equipped with an Arduino Uno, infrared sensors, and other components that allow for high-precision navigation. The research results show that the line follower robot successfully followed the predetermined path and delivered food efficiently. The evaluation indicates that the robot's speed needs to be adjusted according to the load to avoid deviation from the path. This research provides significant contributions to improving operational efficiency and customer satisfaction in the food and beverage industry.